Value-based management: Theoretical base, shareholders' request and the concept - Kaličanin Đorđe M. (Ekonomski Anali, 2005)
The pressure of financial markets, which is a consequence of shareholder revolution, directly affects the solution to the following dilemma: is the mission of corporations to maximize shareholders' wealth or to satisfy interests of other stakeholders? The domination of shareholder theory has caused the appearance of the valuebased management concept. Value-based management is a relevant concept and a process of management in modern environment. The importance of shareholder value requires transformation of traditional enterprise into value driven enterprise. This paper addresses theoretical base, shareholder revolution and the main characteristics of value-based management.